ASSOCIAÇÃO ENTRE CARACTERÍSTICAS INFANTIS E ESTRESSE DE ALUNOS DE GRADUAÇÃO DURANTE ATENDIMENTO ODONTOPEDIÁTRICO - Oliveira, Thays Torres do Vale (2022)
Objective: The aim of this study was to evaluate the association between thecharacteristics of children and the stress presented by undergraduate dentistry students during pediatric dental care. Materials and Methods: Participants were 48 children aged between 6 to 10 years old and 37 volunteer students from the 7th,8th and 9th semesters of a Dentistry course. A questionnaire on socioeconomic aspects was carried out and data on behavior, perception of pain and anxiety of the child and the guardian were also collected. Also, data related to undergraduatestudents were collected: sex, semester, stress level, type of procedure performed. Absolute and relative frequencies were obtained through descriptive data analysis. Comparisons in the outcomes of interest were made using the chi-square test for dichotomous and categorical variables, linear by linear test for ordinal variable, and Fisher’s exact test for counts less than 5. A significance level of 5% was adopted. Results: The results showed that students who assisted non-cooperative children reported a high level of stress (83.33%) (p<0.001). Students who assisted children with medium or high levels of anxiety reported high levels of stress.(p=0.043) and in patients with pain, the students’ stress level was considered high (75%) (p=0.001). Conclusion: The characteristics of the children influenced the stress presented by the student during child dental care. Anxious children, noncooperative and who were in pain during care left the student more stressed.